2012
DOI: 10.18553/jmcp.2012.18.9.701
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use Patterns and Predictors of Nonpersistence and Nonadherence with Oral 5-Aminosalicylic Acid Therapy

Abstract: BACKGROUND: 5-aminosalicylic acid (5-ASA) is the recommended firstline treatment for active mild-to-moderate ulcerative colitis (UC) and for maintenance of UC remission. However, persistence and adherence to prescribed 5-ASAs are often suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
2
29
1
1
Order By: Relevance
“…serum drug levels, clinical drug effects) 11. Patients with an average MPR ≥80% were classed as adherent; this is in line with previous adherence studies conducted in IBD 612. Patients with an average MPR >200% over the whole study period were excluded from the analysis.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…serum drug levels, clinical drug effects) 11. Patients with an average MPR ≥80% were classed as adherent; this is in line with previous adherence studies conducted in IBD 612. Patients with an average MPR >200% over the whole study period were excluded from the analysis.…”
Section: Methodssupporting
confidence: 57%
“…11 Patients with an average MPR ≥80% were classed as adherent; this is in line with previous adherence studies conducted in IBD. 6,12 Patients with an average MPR >200% over the whole study period were excluded from the analysis. Ostensibly, excessive adherence rates typically arise through anomalies in dispensing or refill practice, for example, if a patient receives half of their prescribed medication in one dispensing followed by the remainder the following day, they would record an MPR of several thousand per cent.…”
Section: Study Evaluations and Measuresmentioning
confidence: 99%
“…Yen et al 22 reported in 2012 found that being younger than 65 years and being female were independently associated with nonadherence in the real world. Our study population generated different conclusions; older patients and females were less adherent to rectal administration.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Our understanding of adherence behavior in patients with IBD is thus incomplete, as the methodology of many studies only allows examination of surrogate markers of beliefs or behaviors, such as gender or socioeconomic status, rather than patient-reported barriers to adherence. 2,18,19 Data from other diseases have identified patient-reported barriers to adherence, but these results may not be applicable to the IBD population because of the different demographic distributions of these conditions; the concerns of a woman aged 50 years with breast cancer may not mirror those of a college student aged 20 years with colitis. 20 Qualitative-based research has illustrated that enhancing medication-taking behavior in patients with IBD requires a more in-depth examination of patients' motivations.…”
Section: What This Study Addsmentioning
confidence: 99%